Call blocking and outage probability in energy‐efficient LTE networks. Issue 10 (19th April 2018) - Kanwal, Kapil; Safdar, Ghazanfar Ali; Rehman, Masood Ur
Abstract: Mobile operators are continuously expanding network infrastructure through the deployment of additional base stations to satisfy ever growing user demands. In parallel, number of users is also increasing due to advancement in mobile applications. Enlarged number of users and base stations introduce major problems, such as call blocking and outage probability, due to limited resources and interference caused by frequency reuse, respectively. Both these parameters play a key role in estimation of overall system performance. Alongside, energy efficiency (EE) is a vital parameter to enable portability and longevity of mobile user equipment. This paper investigates call blocking and channel outage probability in reduced early handover (REHO) deployed Long‐Term Evolution networks. System level simulations are performed in MATLAB to analyze the performance of REHO before it is compared with Long‐Term Evolution standard and other state of the art for key performance‐related parameters including EE, outage probability, and call blocking probability. Besides increased EE, REHO is also found to be competitive enough in terms of call blocking probability in the presence of Poisson process call arrivals. Abstract : This paper addresses mobility management in 4G/5G networks and provides performance analysis of Reduced Early Handover (REHO) scheme by collectively investigating the impact of energy saving on call blocking and channel outage probability in Long Term Evolution networks.